Neophytie unter arealkundlichen und standortökologischen Aspekten, dargestellt an einer Fallstudie aus dem Flußgebiet der Eifel-Ruhr / Westdeutschland - Kasperek, Gerwin (ERDKUNDE, 1999)
Immigration of plants in the wake of man (anthropochory), and especially immigration of neophytes since the 16th century (neophytism) touch on the disciplines chorology and site-ecology. There are different, partly contrasting ways of looking at the phenomenon in both disciplines. By means of a case study from Germany which viewpoints serve best in analysing cases of neophytism are determined. Using distribution data of five neophytes on river banks (Impatiens glandulifera, Bidens frondosa, Galinsoga ciliata, Heracleum mantegazzianum, Fallopia japonica), factors are discussed which faciliated or promoted spread. Effects of different scales of investigation in the case study are stressed. Percentages of archaeophytes and neophytes, for example, behaved differently when the scale of sampling was changed. The contrast between chorological and site-ecological viewpoints is partly a matter of scale, too. Anthropogenic alterations of site conditions do promote some neophytes, but by no means all of them. Plant migrations bear an irreversible historical character. Consequences for controlling of neophytes are discussed; in Central Europe, such measures only make sense in exceptional cases. In the long run, inclusion of anthropogeographical elements will be useful for a comprehensive understanding of neophytism.